Body and Language in Eating Disorders - Domenico Cosenza (EJP import test, 2017)
Summary: In this text[1] we will try to question the symptoms that descriptive psychiatry classifies as eating disorders—anorexia, bulimia, and binge-eating disorder—from the perspective of a Lacanian psychoanalytic approach. The key points of this discussion will be the themes of body and language in the clinical treatment of anorexia, bulimia and psychogenic obesity. These symptoms, so widespread today, can teach us much about the topic of the recent Congress of the World Association of Psychoanalysis on “The Speaking Body. On the Unconscious in the 21st Century”. The clinical treatment of eating disorders forces us to question the status of the body in its narcissistic image, symbolic structure, and functioning, as a place that condenses jouissance for the speaking being. Indeed, a negative passion for the mirror, a holophrastic dimension in the functioning of speech and language, and a limitless compulsive jouissance, are key factors in this field in contemporary clinical treatment.
Keywords: Body of the Image; Eating Disorders; Holophrases; language; Psychoanalysis